Relocation and expansion planning for dairy producers - John F. Smith; Joseph P. Harner; D. V. Armstrong; M. J. Gamroth (Kansas Agricultural Experiment Station Research Reports, 1999)
Relocating or expanding a dairy facility requires a tremendous amount of time and planning. Owners or managers of dairies will go through a number of steps including: 1) developing a business plan; 2) choosing a design process; 3) developing specifications; 4) selecting location/site; 5) obtaining permits/ legal; 6) obtaining bids; 7) selecting contractors; 8) buying cattle; 9) purchasing feeds; 10) financing; 11) managing construction; 12) hiring and training employees; 13) developing management protocols for the dairy; and 14) managing information flow. The dairy can be divided into these components: 1) milking parlor; 2) cow housing; 3) special needs facility (e.g., hospital, closeups); 4) replacement heifer housing; 5) manure management system; and 6) feed center. This article will focus on milking parlors, cow housing, grouping strategies, and site selection.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Dairy facilities; Expansion; Cow comfort